2022
DOI: 10.47305/jlia2281051k
|View full text |Cite
|
Sign up to set email alerts
|

The Challenging Factors Affecting Women Entrepreneurial Activities

Abstract: The purpose of this study is to investigate the factors such as access to finance, legal constraints, and entrepreneurial skill on women's participation in business activities. The mediating effects of self-leadership were also established as an influence on women's participation in business activities. Moreover, the study examined the moderating effect of education among selfleadership and participation of women in entrepreneurial activities. The study selected a quantitative method and structured questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
1
7
0
4
Order By: Relevance
“…The majority of the female entrepreneurs depended entirely on the personal savings they accumulated through their human capital over the years to establish and operate their enterprises. This finding is in line with a more general observation that access to finance remains a major challenge for female entrepreneurs (Khalid et al, 2022).…”
Section: Resource Gatheringsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of the female entrepreneurs depended entirely on the personal savings they accumulated through their human capital over the years to establish and operate their enterprises. This finding is in line with a more general observation that access to finance remains a major challenge for female entrepreneurs (Khalid et al, 2022).…”
Section: Resource Gatheringsupporting
confidence: 91%
“…Among the five categories of Entrepreneurship as emancipation capital, economic capital in the form of financial resources and other physical assets was the most crucial. This reflects that access to financial resources remains one of the most essential elements for starting and successfully running a venture profitably (Khalid et al, 2022).…”
Section: Resource Gatheringmentioning
confidence: 99%
“…The dimensions of corporate social responsibility state the structures which could bring significant performance. These dimensions are positively stated by the relativeness of financial capacity and the demanding needs of consumers in COVID-19 ( Khalid et al, 2022 ). Therefore, economic, social, and environmental elements are positive approaches of corporate social responsibility which states the image of companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study found a significant relationship between the effect of access to legal constraints in business activities and reported that legal constraints were one of the challenging factors affecting entrepreneurial activities in entrepreneurial (Khalid et al, 2022).…”
Section: Scaling Challengesmentioning
confidence: 99%